Powiązania cen wieprzowiny w Polsce z cenami europejskimi - Hamulczuk, Mariusz (Connection of Domestic Pork Prices with European Prices, 2006)
The aim of the paper is the comparison of the pork prices fluctuation in Poland and in the selected European countries. An analysis indicates that the connection of the Polish pork prices with European prices has been existed especially since 1988. The convergence of the long-term relationship has been more evident than the short-term interaction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 299-304